An airway epithelial iNOS–DUOX2–thyroid peroxidase metabolome drives Th1/Th2 nitrative stress in human severe asthma - Voraphani, N; Gladwin, M T; Contreras, A U; Kaminski, N; Tedrow, J R; Milosevic, J; Bleecker, E R; Meyers, D A; Ray, A; Ray, P; Erzurum, S C; Busse, W W; et al. (Mucosal immunology, 2014)
Severe refractory asthma is associated with enhanced nitrative stress. To determine the mechanisms for high nitrative stress in human severe asthma (SA), 3-nitrotyrosine (3NT) was compared with Th1 and Th2 cytokine expression. In SA, high 3NT levels were associated with high interferon (IFN)-γ and low interleukin (IL)-13 expression, both of which have been reported to increase inducible nitric oxide synthase (iNOS) in human airway epithelial cells (HAECs). We found that IL-13 and IFN-γ synergistically enhanced iNOS, nitrite, and 3NT, corresponding with increased H2O2. Catalase inhibited whereas superoxide dismutase enhanced 3NT formation, supporting a critical role for H2O2, but not peroxynitrite, in 3NT generation. Dual oxidase-2 (DUOX2), central to H2O2 formation, was also synergistically induced by IL-13 and IFN-γ. The catalysis of nitrite and H2O2 to nitrogen dioxide radical (NO2•) requires an endogenous peroxidase in this epithelial cell system. Thyroid peroxidase (TPO) was identified by microarray analysis ex vivo as a gene distinguishing HAEC of SA from controls. IFN-γ induced TPO in HAEC and small interfering RNA knockdown decreased nitrated tyrosine residues. Ex vivo, DUOX2, TPO, and iNOS were higher in SA and correlated with 3NT. Thus, a novel iNOS–DUOX2–TPO–NO2• metabolome drives nitrative stress in HAEC and likely in SA.